Polypharmacy in African American Adults: A National Epidemiological Study - Shervin Assari; Hamid Helmi; Mohsen Bazargan (MDPI AG, 2019)
Background: Despite the association between polypharmacy and undesired health outcomes being well established, very little is known about epidemiology of polypharmacy in the African American community. We are not aware of any nationally representative studies that have described the socioeconomic, behavioral, and health determinants of polypharmacy among African Americans. Aims: We aimed to investigate the socioeconomic and health correlates of polypharmacy in a national sample of African American adults in the US. Methods: The National Survey of American Life (NSAL, 2003–2004) included 3,570 African American adults. Gender, age, socioeconomic status (SES; education attainment, poverty index, and marital status), access to the healthcare system (health insurance and having a usual source of care), and health (self-rated health [SRH], chronic medical disease, and psychiatric disorders) in addition to polypharmacy (5 + medications) as well as hyper-polypharmacy (10 + medications) were measured. Logistic regressions were applied for statistical analysis. Results: that About 9% and 1% of all African American adults had polypharmacy and hyper-polypharmacy, respectively. Overall, higher age, higher SES (education and poverty index), and worse health (poor SRH, more chronic medical disease, and psychiatric disorders) were associated with polypharmacy and hyper-polypharmacy. Individuals with insurance and those with a routine place for healthcare also had higher odds of polypharmacy and hyper-polypharmacy. Conclusions: Given the health risks associated with polypharmacy, there is a need for systemic evaluation of medication use in older African Americans with multiple chronic conditions. Such policies may prevent medication errors and harmful drug interactions, however, they require effective strategies that are tailored to African Americans.